2010
DOI: 10.3109/13651501.2010.519035
|View full text |Cite
|
Sign up to set email alerts
|

Global assessment of psychosocial functioning and predictors of outcome in schizophrenia

Abstract: Our preliminary results suggest that psychosocial outcome in schizophrenia may be affected by different factors. Longer history of psychotic episodes emerged as the most significant determinant of poorer outcome while longer duration of untreated illness and older age at illness onset were also associated with detrimental effects. Our findings may reflect the combined influences of neurodevelopmental abnormalities, exposure to psychotropic medication and psychosocial interventions as well as the vicissitudes o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Lastly, we should also acknowledge the absence of clinical measures, aside from apathetic social withdrawal and depressed mood. Studies showed that clinical variables, including positive and negative symptoms as well as the course of illness, are associated with poorer levels of everyday functioning (Smith et al, 2002; Stefanopoulou et al, 2011). However, the literature argues that psychopathology has a relatively low predictive value of daily functioning, since the functional disruption persists after achieving a psychopathological stabilization (González-Blanch et al, 2010; Menezes et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, we should also acknowledge the absence of clinical measures, aside from apathetic social withdrawal and depressed mood. Studies showed that clinical variables, including positive and negative symptoms as well as the course of illness, are associated with poorer levels of everyday functioning (Smith et al, 2002; Stefanopoulou et al, 2011). However, the literature argues that psychopathology has a relatively low predictive value of daily functioning, since the functional disruption persists after achieving a psychopathological stabilization (González-Blanch et al, 2010; Menezes et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Age at onset is one of the most commonly analysed predictor of outcome in schizophrenia but the results obtained in different original studies are far from conclusive: some have found a lower age at onset to have a positive effect on outcomes (Bland & Parker, ; Bland, Parker, & Orn, ; Stefanopoulou et al, ; Stephens, Richard, & McHugh, ), some a negative effect (Altamura, Bassetti, Sassella, Salvadori, & Mundo, ; Juola, Miettunen, Veijola, Isohanni, & Jääskeläinen, ) and others no effect at all (Üçok, Gorwood, & Karadayı, ). In their systematic review, Menezes and colleagues studied age at onset alongside other predictors of “good” and “bad” outcomes, functional recovery, intermediate outcome, relapse, readmission, Global Assessment of Functioning (GAF) Scale and employment/education in first‐episode psychosis.…”
Section: Introductionmentioning
confidence: 99%
“…Positive and negative symptoms have been consistently found to be minimally related to functional competence, but they are often found to be associated with poorer everyday real world performance even after other factors, such as functional competence, are considered (e.g., Bowie et al, 2006; 2008; 2010; Leifker et al, 2009; Sabbag et al, 2012; Smith et al, 2002; Stefanoloulou et al, 2011). Positive symptoms tend to respond well to pharmaceutical treatment, but approximately 15-20% of people with schizophrenia experience treatment-resistant negative symptoms (Buchanan, 2007) that are strongly associated with poor functional outcomes (e.g., Herbernet & Harrow, 2004; Milev et al, 2005; Leifker et al, 2009; Sabbag et al, 2012).…”
Section: Introductionmentioning
confidence: 99%